Utilization of social networking sites by small home-based business - Percol, Dianne Kamille L.
ABSTRACT This study examined the use of social networking sites (SNSs) by small home-based enterprises. Specifically, it described the business functions wherein social networking sites are utilized; and analyzed the strengths, opportunities, weaknesses and threats of utilizing SNSs for business operations.